Introduction pages, NBHA-CN 53(2), 2025 - Radu E. SESTRAS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The papers published in Notulae Botanicae Horti Agrobotanici Cluj-Napoca, Issue 2, Volume 53, 2025, represent new exciting research in different topics of life science, respectively in plant science, horticulture, agronomy, crop science, and forestry. Among the interesting articles, we invite you to find news about: Amplicon sequencing reveals different microbial communities between growing and non-growing seasons in the soils of Pinus armandi forestland in Shennongjia, China; Enhancing phytochemical content and bioactive aspects in somatic embryogenesis developed from callus of Phoenix dactylifera L.; Assessment of genetic architecture of cotton germplasm for drought tolerance: A focus on morpho-physiological and biochemical attributes; Diversity and effectiveness of arbuscular mycorrhizal fungi species in alleviating drought stress in tomato; Site-specific factors influencing Hymenoscyphus fraxineus spore dispersal: the role of understorey vegetation and slope steepness in ash dieback spread; Genetic characterization of Greek chestnut (Castanea sativa Mill.) germplasm collections in Parnon mountain; Syringa josikaea (Oleaceae) biotopes in the Ukrainian Carpathians: Climatic conditions and current dynamics; Propagation and community perspective of the climber species Smilax nageliana A.DC. endemic to Java Island; Improvement of quality, physiological parameters and antioxidant status of chrysanthemum by priming of seedlings with UV-A radiation; Silicon dioxide nanoparticles a strategy to improve the growth, physiology, yield, and nutraceutical quality of tomatoes.